Bifidobacterium animalis subsp. lactis and arginine mixture intake improves cognitive flexibility in mice - Ikuta, Kayo; Joho, Daisuke; Kakeyama, Masaki; Matsumoto, Mitsuharu (Frontiers in Nutrition, 2023)
The relationship between intestinal microbiota and cognitive function has been investigated as one of the major topics within the intestinal microbiota-gut-brain axis. Although an increasing number of studies show an improvement in learning and memory when using pro- or prebiotics, there are no studies targeting the cognitive flexibility observed in the early stages of several neuropsychiatric diseases, including dementia. We have recently developed a novel behavioral task using the touch screen operant system to assess cognitive flexibility. We found that the disruption of intestinal microbiota in mice induced a decline in cognitive flexibility. In the present study, we investigated the effects of treatments consisting of Bifidobacterium animalis subsp. lactis and arginine (Bifal+Arg), which promote intestinal bacterial polyamine production on mouse cognitive flexibility. Male C57BL6 mice orally treated with Bifal+Arg three times a week gradually decreased in the 1st-choice incorrect choices with repeated reversals compared with control mice. Furthermore, in serial reversal phases, Bifal+Arg-treated mice shifted to the behavior of choosing a new correct spot more quickly after the reversal, and this was faster with repeated reversals. These results indicate that this treatment adapts to change and improves cognitive flexibility. This is the first report to show that intestinal environmental control, including pro- and prebiotics, improves cognitive flexibility in mice.